2014
DOI: 10.3109/00365521.2014.920915
|View full text |Cite
|
Sign up to set email alerts
|

Capsule endoscopic findings correlate with fecal calprotectin and C-reactive protein in patients with suspected small-bowel Crohn’s disease

Abstract: Inflammatory lesions in the small bowel diagnosed by CE in patients with suspected Crohn´s disease are correlated to fecal calprotectin and CRP, but not to symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…Höög et al [7], in a cohort of 30 patients, showed that there was a significant persistent correlation between endoscopic inflammation and FC (at study inclusion and at a year's follow-up). More recently, Olsen et al showed that the proportion of patients with findings on small-bowel CE increased with increasing FC [30].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Höög et al [7], in a cohort of 30 patients, showed that there was a significant persistent correlation between endoscopic inflammation and FC (at study inclusion and at a year's follow-up). More recently, Olsen et al showed that the proportion of patients with findings on small-bowel CE increased with increasing FC [30].…”
Section: Discussionmentioning
confidence: 96%
“…In this single-center study, FC [ 100 lg/g is good predictor of positive smallbowel CE findings, while FC [ 200 lg/g was associated with higher CE diagnostic yield (65 %) and confirmed small-bowel inflammation in 50 % of cases. Hence, it is reasonable to consider that strong correlation should exist between FC levels and LS [7][8][9]. However, in a separate cohort of patients with suspected, isolated small-bowel disease, LS showed strong correlation with FC at levels \100 lg/g [8].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies have been published trying to assess the association between symptoms (7,28) or isolated biomarkers with the presence of inflammatory lesions in CE. Regarding laboratory tests, we found some case series in the literature about the usefulness of fecal markers (most of them on FC), with heterogeneous and sometimes conflicting results (8,13,29,30). There are only a few short case series analyzing the association between symptoms and biomarkers together with findings in CE.…”
Section: Discussionmentioning
confidence: 99%
“…Faecal neutrophil-derived protein, calprotectin, is sensitive but not a disease-specific surrogate marker for intestinal inflammation [5, 6]. While there is growing acceptance of FC as a valuable biomarker of colonic IBD, and there is evidence to show FC correlates with SB inflammation, data on the ability of this faecal biomarker to detect and out rule SB abnormalities in unselected patients is less clear [7]. The clinical role of faecal and serum biomarkers in predicting findings compatible with SB CD as assessed by SBCE in particular has been insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%